Media concentration and democracy : why ownership matters - Baker, C. Edwin (Cambridge ; New York : Cambridge University Press, 2007)
"Objections to concentrated ownership of the mass media are widespread. Often, however, critics merely point to the fact of huge and growing media conglomerates without explaining precisely why this is bad. This book fills the gap in the critique of concentration. Firmly rooting its argument in democratic and economic theory, the book argues that a more democratic distribution of communicative power within the public sphere and a structure that provides safeguards against abuse of media power provide two of three primary arguments for ownership dispersal. It also shows that dispersal is likely to result in more owners who will reasonably pursue socially valuable journalistic or creative objectives rather than a socially dysfunctional focus on the "bottom line." The middle chapters answer those, including the current Federal Communications Commission, who favor "deregulation" and who argue that existing or foreseeable ownership concentration is not a problem. The final chapter evaluates the constitutionality and desirability of various policy responses to concentration, including strict limits on media mergers."--Jacket
Democracy at the crossroads: why ownership matters -- Not a real problem: many owners, many sources -- Not a real problem: the market or the internet will provide -- The First Amendment guarantee of a free press: an objection to regulation? -- Solutions and responses -- Postscript: policy opportunism.
Includes bibliographical references (pages 203-248) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Umschulungswerkstätten für Siedler und Auswanderer; Mass media -- Ownership -- United States; Freedom of the press -- United States; Médias -- Propriété -- États-Unis.; Liberté de la presse -- États-Unis.; SOCIAL SCIENCE -- Media Studies; Mass media -- Ownership -- United States; Freedom of the press -- United States; Freedom of the press; Mass media -- Ownership; United States; Demokratie; Massenmedien; Unternehmenskonzentration; Eigentümer; Pressefreiheit; Mass media -- Ownership -- United States; Freedom of the press -- United States; Mediekoncentration; Electronic books; Electronic books